Maps of student genres in engineering: a didactic model for teaching academic and professional Spanish language - lvalue lvalue; Enrique Sologuren Insúa (Universitat Jaume I. Department of English Studies, 2020)
Enrique Sologuren Insúa Universidad de Chile, Chile   ABSTRACT Textual genres written by university students have become the focus of attention due to its importance and a wide range of functions within disciplinary learning (Parodi 2010). This paper centres on the field of study known as student genres (Navarro 2018) and it uses the analysis of situated genre (Swales 2018, Perez-Llantada 2015) as the methodological platform. This study aims to develop two main objectives: a) to create a map of student genres from a learner corpus of the engineering field, and b) to propose a didactic model for teaching academic and professional Spanish language using this map. In this way, linguistic research and description are linked to pedagogical needs (Breeze and Sancho Guinda 2017) and take into account the actual practice in the communities, as well as the writers in these disciplines (Curry and Hanauer 2014). Finally, implications for configuring specific didactics in LSP are discussed.